A novel recyclable BiOCl/BiOI/MnxZn1-xFe2O4 photocatalyst with enhanced Rhodamine B removal under visible light. (November 2022) - Zhang, Qiyuan; Yang, Zhengxin; Zhang, Ru; Hao, Yu; Xu, Longjun; Liu, Chenglun
Abstract: A novel recyclable BiOCl/BiOI/Mnx Zn1-x Fe2 O4 photocatalyst has been synthesized using a hydrothermal way. Herein, the photocatalytic performances of BiOCl/BiOI combined with different mass ratios of Mnx Zn1-x Fe2 O4 were displayed through degrading Rhodamine B (RhB) under simulated visible light. Among the fabricated samples, BiOCl/BiOI with 3 wt% Mnx Zn1-x Fe2 O4 (BCI-3MZF) possessed the best photocatalytic activity, which could remove 98% RhB within 40 min owing to the larger specific area (84.82 m 2  g −1 ) and small bandgap energy (2.13 eV). The recyclability test showed that the saturation magnetization of BCI-3MZF was 2.65 emu·g −1, which meant that this photocatalyst could be recovered conveniently through an external magnetic field. Furthermore, the stability test demonstrated that the degradation ratio of RhB using BCI-3MZF could still exceed 90% after using four times. In the basis of these results, a possible photodegradation process was analyzed and illustrated. The investigation of BiOCl/BiOI/Mnx Zn1-x Fe2 O4 may provide the field of photocatalysis with a new perspective to treat wastewater and protect the environment. Highlights: A novel recyclable BiOCl/BiOI/Mnx Zn1-x Fe2 O4 photocatalyst was synthesized. The internal magnetic field could conduce to boosting the photodegradation. The possible photodegradation mechanism was proposed.